Stroke prevention by Non-vitamin K Oral Anticoagulant (NOAC) agents in the absence of atrial fibrillation: meta-analysis of randomized control trials. (25th November 2020) - Lander, K; Thakeria, P; Andrew, H; Nayyar, S
Abstract: Background: Anticoagulation to prevent stroke is a mainstay of atrial fibrillation (AF) management. Patients with established cardiovascular disease (CVD) may have conditions that fulfil Virchow's triad for thrombogenesis even in sinus rhythm. Previous investigation into the benefit of warfarin compared to placebo or antiplatelet drug in sinus rhythm found a reduction in stroke rates, but with an increase in bleeding. The efficacy and safety of non-vitamin K oral anticoagulant (NOAC) agents has not been studied. Purpose: To assess the safety and efficacy of NOAC agents in patients without AF. Methods: An electronic database search for randomized controlled trials that evaluated a NOAC and control drug (placebo or antiplatelet) in non-AF patients with CVD was conducted up until 1 September 2019. The primary efficacy and safety outcomes were ischemic stroke and major bleeding, respectively. The net clinical benefit (NCB) was calculated as a weighted sum of rate differences of ischemic stroke and major bleeding. Groups were stratified according to intensity of anticoagulation (full vs. low dose NOAC). Results: Twelve randomized controlled trials were identified with a total of 83, 008 patients (50, 617 on NOAC, 32391 on control drug; mean age 66±2.7 years). CVD included coronary artery disease (78.3%), hypertension (73.7%), diabetes mellitus (34.7%), peripheral arterial disease (30.3%), previous stroke (21.7%), renal disease (22.9%) and heart failure (18.4%). Over a mean follow-up of 17.3 months, 1347 (1.6%) ischemic strokes occurred. Use of NOAC was associated with 28% reduction in ischemic stroke (odds-ratio [OR] 0.72, 95% confidence-interval [CI] 0.60 to 0.87; 1.1 vs. 1.8 events per 100-person years), with numbers needed to treat of 145 patients to prevent one stroke. Major bleeding was increased nearly 2-fold (OR 1.83, 95% CI 1.46 to 2.29; 2.1 vs. 1.0 events per 100-person years). The NCB demonstrated overall harm with the use of NOAC agents in this patient population (NCB = −0.28, 95% CI: −0.79 to 0.23). Use of full dose NOAC was widely unsafe (NCB = −0.35, 95% CI: −1.25 to 0.54) and low dose NOAC approached null therapeutic safety advantage (NCB = −0.06, 95% CI: −0.47 to 0.35). Conclusion: Patients with CVD are at increased of ischemic stroke in the absence of AF. The use of NOAC agents in this non-AF population reduces rate of ischemic stroke however overall risk of bleeding exceeds antithrombotic benefit. Low-dose NOACs demonstrate a neutral NCB suggesting a point of clinical equipoise and deserve further scrutiny. Funding Acknowledgement: Type of funding source: None